2014
DOI: 10.1111/jbi.12321
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering overlooked island diversity: colonization and diversification of the medically important spider genus Loxosceles (Arachnida: Sicariidae) on the Canary Islands

Abstract: Aim Our aim was to assess the evolutionary history of the spider genus Loxosceles on the Canary Islands. We unravelled its present diversity within the archipelago, and investigated its origin, mode and tempo of colonization to and between the islands using a phylogenetic framework.Location Canary Islands, Madeira, Iberian Peninsula, North Africa, Mediterranean region, Guinea.Methods We conducted extensive sampling across the Canary Islands, and examined the phylogenetic relationships among the Canary Island r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 62 publications
2
42
0
Order By: Relevance
“…While extant liphistiids indeed possess arachnid plesiomorphies (figure 1a,b) not shared with any other spiders, and the Mesothelae lineage traces back as far as the Carboniferous, the origin of Liphistiidae and its diversification are surprisingly much more recent than once thought, repeating the patterns recently detected also in other textbook living fossils [1,4]. We trace the origin of the family in Southeast or East Asia to the Late Palaeogene and Eocene (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), and the origins of all eight genera to the Late Oligocene and Neogene (figure 3a; electronic supplementary material, figure S1 and table S3). However, liphistiids do belong to a very long evolutionary branch that connects them with the only mesothelean fossil known from Eurasia ( figure 3a), and consequently, some of their phenotypic traits resemble the hypothetically ancestral spiders.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While extant liphistiids indeed possess arachnid plesiomorphies (figure 1a,b) not shared with any other spiders, and the Mesothelae lineage traces back as far as the Carboniferous, the origin of Liphistiidae and its diversification are surprisingly much more recent than once thought, repeating the patterns recently detected also in other textbook living fossils [1,4]. We trace the origin of the family in Southeast or East Asia to the Late Palaeogene and Eocene (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), and the origins of all eight genera to the Late Oligocene and Neogene (figure 3a; electronic supplementary material, figure S1 and table S3). However, liphistiids do belong to a very long evolutionary branch that connects them with the only mesothelean fossil known from Eurasia ( figure 3a), and consequently, some of their phenotypic traits resemble the hypothetically ancestral spiders.…”
Section: Discussionsupporting
confidence: 78%
“…All phylogenetic analyses support the monophyly of Liphistiidae and of eight genera. As the fossil evidence supports a Carboniferous Euramerican origin of Mesothelae, our dating analyses postulate a long eastward over-land dispersal towards the Asian origin of Liphistiidae during the Palaeogene (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). Contrary to expectations, diversification within extant liphistiid genera is relatively recent, in the Neogene and Late Palaeogene .…”
mentioning
confidence: 64%
“…However, species may, at least sometimes, also disperse from younger to older islands, even when these islands are occupied by close relatives (70). Among spiders, a progression rule has been documented for Loxosceles (73) and Dysdera (74, 75), whereas Pholcus and Spermophorides probably colonized the older Fuerteventura and Lanzarote from the younger Gran Canaria (76,77). The mixed support for a progression across the Canary Islands presents the possibility of an alternative explanation for the origin of the endemics of the oldest islands, which could be the result of secondary replacement of its original fauna by new colonists better adapted to increasingly arid conditions (78).…”
Section: The Progression Rule In Comparative Island Phylogeographymentioning
confidence: 99%
“…The "stepping-stone by island age model" of asymmetric colonization from geologically older to younger islands is one of the common modes of colonization in several well-documented archipelagos, showing a clear linear age sequence of the origin of islands, such as the Hawaiian and Gal apagos Islands in the Pacific Ocean (Funk & Wagner, 1995;Gillespie, 2004;Parent, Caccone, & Petren, 2008) and the Canary Islands in the Atlantic (Juan et al, 2000;Planas & Ribera, 2014). However, some observations of stochastic dispersal have suggested that the unpredictability of interisland colonization can be linked to the geological history of the islands in a more complex manner (Gillespie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%